Numerical exploration on n-decane nanofluid based MHD mixed convection in a lid driven cavity: impact of magnetic field and thermal radiation - Umme Habiba; M.N. Hudha; Badhan Neogi; Saiful Islam; M.M. Rahman (International Journal of Thermofluids)
Due to efficient heat transfer properties, nanofluids have become the core of research in the present world in the sectors of engineering, biotechnology, pharmaceutical industries, etc. The present work prioritizes the numerical assessment of n-decane/graphite nanofluid MHD mixed convective flow within a lid-driven trapezoidal barrier with radiation effect, where the left and right bottom, the side walls are kept thermally insulated, the upper wall (moving with uniform velocity, u0) is in cold temperature (Tc) and a rectangular heater (with temperature, Th) is placed in the middle of the bottom wall of the enclosure. The numerical executions of governing equations are conducted by finite element method. The resulting parameters, Hartmann number (Ha = 0, 30, 50 and 80), solid nanoparticle volume fraction (ϕ = 1 %, 5 %, 10 % and 15 %), radiation parameter (Rd = 0, 2, 3 and 4), Reynolds number (Re = 100, 200, 300 and 400) depict the result in terms of streamlines, isothermal contours, average Nusselt number (Nuav), average velocity (Vav). It is noticed that the Hartmann number has a negative influence on fluid flow, which diminishes the vortex strength, average heat transfer rate and average velocity in all cases. In the present case, mixing additional solid nanoparticles in the base fluid augments the Nuav that is being transferred from the source to the fluid, but it lessens the flow strength and average velocity. An increase in Rd elevates the streamline vortex strength and average velocity; in contrast, Nuav is dropped by the Radiation parameter. The Reynolds number appears to have a positive impact on the overall phenomena as it gives rise to all the streamlined vortex strength, Nuav and Vav. This study provides new insights into fluid flow characteristics and heat transfer enhancement in a hydrocarbon-based nanofluid system by combining the influence of thermal radiation and different magnetic field intensities in a distinctive manner. A new HVAC device can also be designed with this idea.